Українські музейники переймають досвід Лувру - Казанцева, Л.В. (Питання історії науки і техніки, 2009)
В конце 2009 года в Музее искусств им. Варвары и Богдана Ханенко в Киеве состоялся
семинар работников музеев, организованный совместно Украинским центром развития музейного дела Благотворительного фонда «Украина 3000» и Культурным центром Франции в Украине. На семинаре представители Парижского музея Лувр ознакомили украинцев с организацией музейной работы и обучения персонала музеев во Франции. In the end of 2009 in the Museum of arts of a name Barbarian and Bogdan Hanenko in Kiev has
taken place a seminar of workers of the museums, organised by In common Ukrainian centre of development
of museum business of Welfare fund «Ukraine 3000» and the Cultural centre of France in
Ukraine. At a seminar representatives of the Parisian museum the Louver have acquainted Ukrainians
with the organisation of museum work and training of the personnel of museums in France.